ЗАСТОСУВАННЯ ІКТ ПРИ ВИКЛАДАННІ ДИСЦИПЛІН ЦИКЛУ МАШИНОЗНАВСТВА ПІД ЧАС ПІДГОТОВКИ МАЙБУТНІХ УЧИТЕЛІВ ТЕХНОЛОГІЇ - Онищенко, Сергій; Вертипорох, Дмитро (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття є узагальненням досвіду роботи з використання ІКТ в навчанні дисциплін циклу машинознавства. Недостатність ілюстративного матеріалу з дисциплін циклу машинознавства у ВНЗ вирішується шляхом використання мультимедійного устаткування. Тому основною метою використання ІКТ в навчальному процесі є стимулювання і підтримка інтересу студентів до освоєння дисциплін циклу машинознавства. Описуються приклади використання різноманітних мультимедійних ресурсів на заняттях. Розкрито значимість використання ІКТ в навчанні дисциплін циклу машинознавства. Статья является обобщением опыта работы по использованию ИКТ в обучении дисциплинам цикла машиноведения. Недостаточность иллюстративного материала по дисциплинам цикла машиноведения в ВУЗе решается путем использования мультимедийного оборудования. Поэтому основной целью использования ИКТ в учебном процессе является стимулирование и поддержка интереса студентов к освоению дисциплин цикла машиноведения. Описываются примеры использования различных мультимедийных ресурсов на занятиях. Раскрыто значимость использования ИКТ в обучении дисциплинам цикла машиноведения. This paper is the generalization of experience in the use of ICT in teaching the disciplines of Mechanical Engineering cycle. Lack of illustrative material in the disciplines of Mechanical Engineering at the university cycle is solved by the use of multimedia equipment. Therefore, the main purpose of the use of ICT in the educational process is to encourage and support student’s interest in the development cycle of Engineering disciplines. Characterized importance of training future teachers of technology in accordance with the current level of information society. Improved pedagogical skills through the introduction of modern ICT in the learning process. Describes examples of the use of various multimedia resources in the classroom. Revealed the importance of the use of ICT in teaching the disciplines of Mechanical Engineering cycle. Therefore, implementation of information and communication technologies in the educational process and combining them with traditional methods of teaching puts the students need to be prepared for variable forms of education, improved content to accept disciplines of Engineering.